A comparative analysis of total haemoglobin level and red blood cells count in ABO blood groups of healthy adults - Mahapatra, Bibhupada; Chinara, Aurobinda; Purohit, Prasanta (International Journal of Research in Medical Sciences, 2019)
Background: The haemoglobin content and red blood cells counts in four different ABO blood groups in healthy adults remain conflicting with different results. The present study was undertaken to analyse the possible differences in the haemoglobin content and red blood cell counts in health adults in four ABO blood groups. Methods: This prospective study was undertaken in a tertiary health care facility. A total of 227 healthy students were finally included in this study for analysis. The study subjects were belonging to 18-22 years old of both genders. The haemoglobin content was measured by Sahli’s method and ABO blood group typing along with Rh D typing was carried out in all the students. The statistical analyses were carried out by using Graph-Pad Instat. Results: The mean age of the students was 19.91 years with 59.9% being males. Both haemoglobin level and red blood cells counts were significantly high in males compared to females. Blood groups A, B, AB and O was reported in 41(18.06%), 63(27.75%), 15(6.60%) and 108(47.58%) healthy students respectively. conclusion: There was no significant difference was observed in the mean haemoglobin level and red blood cells counts among the four ABO blood groups.